Исследование устойчивости подготовительных выработок глубоких горизонтов в зоне влияния лавы - Наумович, А.Н.; Терещук, Р.Н. (Геотехническая механика, 2009)
Розглянуто способи охорони і підтримки підготовчих виробок у зоні впливу лави. За
допомогою методу еквівалентних матеріалів визначені раціональні заходи щодо підтримки підготовчих виробок у стійкому стані в умовах шахти “Шахтарська-Глибока”. The ways of protection and maintaining of development workings in a band of influence of longwall are surveyed. With the help of a method of equivalent materials the rational measures on
a roadway maintenance in an inconvertible state in conditions of mine “ShakhterskayaGlubokaya” are determined.